On Differential Subordination and Superordination Results of Multivalent Functions Defined by a Linear Operator - Atshan, Waggas Galib; Haneen Zaghir Hassan (Al-Qadisiyah Journal of Pure Science, 2020)
In this paper, we derive some results for multivalent analytic functions defined by linear operator by using differential Subordination and superordination